Frequency of Aerobic Microorganisms Causing Vaginal Infections in Third Trimester of Pregnancy at Lady Reading Hospital Peshawar - Sattar, Qandil; Syed, Wajeeha (Indus Journal of Bioscience Research, 2025)
Background: Pregnancy is a time when vaginal infections are a major concern as they can lead to preterm birth and premature rupture of membranes. Managing these risks requires identifying the microbial pathogens responsible. Further exploration is required to assess the prevalence and associations of aerobic microorganisms (Escherichia coli, Group B Streptococcus, Enterococcus faecalis, Klebsiella pneumoniae, and Methicillin sensitive Staphylococcus aureus) during the third trimester of pregnancy in order to improve pregnancy outcomes. Objective: To determine the frequency of aerobic microorganisms causing vaginal infections in the third trimester of pregnancy at Lady Reading Hospital Peshawar. Study Design: Cross-sectional observational study. Duration and Place of Study: The study was conducted from December 2020 to June 2021 at the Obstetrics and Gynaecology Department, Lady Reading Hospital, Peshawar. Methodology: A total of 164 pregnant women, aged 18-40 years, with singleton pregnancies over 28 weeks gestation, and presenting with vaginal infections lasting more than five days were enrolled. Clinical assessments were performed, and high vaginal swabs were collected for microbiological analysis. The presence of pathogens was determined through laboratory cultures. Results: The mean age of participants was 27.66 ± 2.94 years, with a predominant middle-class socioeconomic status (75%). E. coli was identified in 34.8% of cases, followed by Group B Streptococcus (19.5%), Enterococcus faecalis (17.1%), Methicillin-sensitive Staphylococcus aureus (18.3%), and Klebsiella pneumoniae (9.1%). Statistically significant associations were observed between E. coli prevalence and lower parity (p = 0.039). Conclusion: This study highlights the high prevalence of E. coli, Group B Streptococcus, and Klebsiella pneumoniae as significant pathogens in vaginal infections during pregnancy.